Stone Spout Water Quality for Drinking Purposes in Kathmandu Metropolitan: An Assessment Using Water Quality Index - Yadav, Pramod Kumar; Kandel, Supriya; Adhikari, Bijaya; Shakya, Bindra Devi; Shakya, Sudarshana; Shakya, Pawan Raj (Journal of Nepal Chemical Society, 2025)
Stone spouts, emblematic of the Kathmandu Valley culture, represent traditional water supply systems with religious, cultural, spiritual, and economic importance. The water sources in the valley partially meet the drinking water requirements of the residents. The study aims to assess the water quality of the traditional stone spouts located in Kathmandu Metropolitan City by using the water quality index (WQI). Water samples were collected from twenty stone spouts within the metropolitan area during the pre-monsoon period (May 2024). Ten selected physicochemical parameters viz., electrical conductivity, total dissolved solids, pH, total hardness, ammonia, fluoride, chloride, nitrate, sulfate, and total iron were examined, and the water quality was assessed using the WQI. Ammonia, fluoride, nitrate, and iron were identified as the main issues in many sampled stone spouts exceeding the permissible limits of NDWQS (2022). The results indicated that the WQI values varied between 19 and 330, with the majority of samples collected from the stone spouts classified as grade E, suggesting that they are unsuitable for drinking. Out of the stone spouts examined, only Gyan dhara and Pepsicola dhungedhara fall under grade A according to the WQI. Linear regression analysis indicated that as TDS and iron levels increase, the WQI also increases. Results suggested that prompt measures are needed to properly treat spout water to reduce contaminants. The study’s results are expected to provide the concerned authorities with essential information about the water quality of the Kathmandu metropolitan stone spouts for the continued sustainability of the traditional water supply systems.